Flow injection conductometric system with gas diffusion separation for the determination of Kjeldahl nitrogen in milk and chicken meat - Junsomboon J. (2014)
A simple flow injection (FI) conductometric system with gas diffusion separation was developed for the determination of Kjeldahl nitrogen (or proteins) in milk and chicken meat. The sample was digested according to the Kjeldahl standard method and the digest was diluted and directly injected into the donor stream consisting of 4M NaOH. In alkaline medium, ammonium was converted to ammonia, which diffused through the PTFE membrane to dissolve in an acceptor stream (water). Dissociation of ammonia caused a change in conductance of the acceptor solution, which was linearly proportional to the concentration of ammonium originally present in the injected solution. A conductometric flow through cell and an amplifier circuit was fabricated, which helped improve sensitivity of the conductometric detection system. With using a plumbing Teflon tape as a gas diffusion membrane and without thermostating control of the system, a linear calibration graph in range of 10-100mgL(-1) N-NH(4) was obtained, with detection limit of 1mgL(-1) and good precision (relative standard deviation of 0.3% for 11 replicate injections of 50mgL(-1) N-NH(4)). The developed method was validated by the standard Kjeldahl distillation/titration method for the analysis of milk and chicken meat samples. The proposed system had sample throughput of 35h(-1) and consumed much smaller amounts of chemical than the standard method (275mg vs 17.5g of NaOH per analysis, respectively).